2013
DOI: 10.19041/apstract/2013/2-3/1
|View full text |Cite
|
Sign up to set email alerts
|

Market trends and consumer demand for fresh berries

Abstract: Abstract:We present an analysis of markets for fresh strawberries, blueberries, blackberries and raspberries in the United States during [2008][2009][2010][2011]. We use weekly panel data covering supermarket purchases in 52 cities. The primary goal is to estimate demand elasticities for fresh berries and thereby provide a better understanding of consumer behaviour in response to price changes and the nature of competition among these crops. We estimate fixed and random effects models for double log demand equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 5 publications
1
11
1
Order By: Relevance
“…This assumption is supported mainly by recent estimates of own-price elasticities of retail demand for fresh soft fruit berries in the USA, ranging from -1.26 for strawberries to -1.88 for blackberries, and of cross-price elasticities among the four crops, which are all positive and thus indicate that these crops are substitutes in demand. 32 Moreover, notwithstanding the large production share of the province, expert industry operators expect that a relevant decrease in production in Trentino, due to the effect of the pest, could easily be substituted, not only by other suppliers of the Italian market (mostly in Southern Italy), but also from countries like Spain, Germany and Poland. 26…”
Section: The Soft Fruit Industry In Trentinomentioning
confidence: 99%
“…This assumption is supported mainly by recent estimates of own-price elasticities of retail demand for fresh soft fruit berries in the USA, ranging from -1.26 for strawberries to -1.88 for blackberries, and of cross-price elasticities among the four crops, which are all positive and thus indicate that these crops are substitutes in demand. 32 Moreover, notwithstanding the large production share of the province, expert industry operators expect that a relevant decrease in production in Trentino, due to the effect of the pest, could easily be substituted, not only by other suppliers of the Italian market (mostly in Southern Italy), but also from countries like Spain, Germany and Poland. 26…”
Section: The Soft Fruit Industry In Trentinomentioning
confidence: 99%
“…Sobeková et al [51] reported an elasticity range of 1.25-1.88 for berry fruits, arguing that price was not a major driver in the choice of individual purchases, as purchase of berries is often sporadic and in small quantities. Furthermore, they determined that price did not have a significant impact on the level of household spending.…”
Section: Brand Knowledgementioning
confidence: 99%
“…We selected the academic papers based on relevance, the Production cost not incl. harvest 10,078 (USD/acre) [37] Labor cost 2408 (USD/acre) [37,38] Labor requirement 29 (people/100 acre) [38,39] Strawberries market prices -Available for download at [30] Elasticity -0.66 [40] Production cost not incl. harvest 12,305 (USD/acre) [33] Labor cost 7788 (USD/acre) [33] Labor requirement 95 (people/100 acre) [39] https://doi.org/10.1371/journal.pone.0229774.t001…”
Section: Case Implementationmentioning
confidence: 99%